2021
DOI: 10.1126/scirobotics.abd5483
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory actuator based on stretchable conductive photothermally responsive hydrogel

Abstract: Mimicking biological neuromuscular systems’ sensory motion requires the unification of sensing and actuation in a singular artificial muscle material, which must not only actuate but also sense their own motions. These functionalities would be of great value for soft robotics that seek to achieve multifunctionality and local sensing capabilities approaching natural organisms. Here, we report a soft somatosensitive actuating material using an electrically conductive and photothermally responsive hydrogel, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
142
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 61 publications
0
142
0
Order By: Relevance
“…In addition to the aforementioned applications, we also explored PANSion's potential as a sensorized pneumatic actuator for soft robotics applications (Supplementary Text 7). It is worth highlighting that our PANSion actuator, benefiting from in-situ-grown AgNPs, is self-sensing, a feature usually absent for previously reported cases, or which requires additional post-treatments to be achieved (e.g., surface conductive coating) 5,12,19 . Fig.…”
Section: Self-sensing Actuator Using Pansion Membranementioning
confidence: 97%
“…In addition to the aforementioned applications, we also explored PANSion's potential as a sensorized pneumatic actuator for soft robotics applications (Supplementary Text 7). It is worth highlighting that our PANSion actuator, benefiting from in-situ-grown AgNPs, is self-sensing, a feature usually absent for previously reported cases, or which requires additional post-treatments to be achieved (e.g., surface conductive coating) 5,12,19 . Fig.…”
Section: Self-sensing Actuator Using Pansion Membranementioning
confidence: 97%
“…Kouwer et al presented thermoresponsive polyisocyanopeptide hydrogel networks that mimic cytoskeletal proteins 150 . Based on interpenetrating polymer networks, conductive responsive hydrogels have been developed to realize smart hydrogel artificial muscles with sensing functions 151 , 152 . Zhao et al 152 demonstrated a soft somatosensitive actuator using an interpenetrating polymer double-network of poly(N- isopropylacrylamide) (PNIPAAm) and PANI.…”
Section: Artificial Muscles With Various Actuating Mechanismsmentioning
confidence: 99%
“…In recent years, a lot of advanced intelligent electronic devices have emerged, such as electronic skin, [1][2][3] soft robotics, [4][5][6] and flexible sensors. [7][8][9][10][11] Among them, flexible sensors have attracted wide attention in the field of human health and movement monitoring because they transform complex external mechanical forces into electrical signals that can easily be collected.…”
Section: Introductionmentioning
confidence: 99%